Pembinaan Pemandu Wisata Berbahasa Inggris dan Pelatihan Drama Tari Dewa Mesraman dalam Upaya Mengembangkan Wisata Budaya Desa Paksebali - Ni Ketut Dewi Yulianti; Ni Wayan Mudiasih; Ni Wayan Suratni; Komang Wahyu Dinata (Sekolah Tinggi Kesenian Wilwatikta (STKW) Surabaya, 2023)
Community Service (PKM) is one of the three dharmas in the Tridharma of Higher Education which is tasked with making the life of the nation and state intelligent and advancing the welfare of society by utilizing educational knowledge in addition to the dharma of research and the dharma of education and teaching. Based on this, ISI Denpasar in 2023 will carry out PKM activities in Paksebali village, Klungkung Regency with the activity title